2022
DOI: 10.1177/15588661221125469
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Campus Recreation and Sport-Based Experience Literature in Higher Education Contexts

Abstract: This rapid review was conducted to synthesize the empirical research related to campus recreation participatory experiences that was published between 2011 and 2021. To carry out the review, three databases (SPORTDiscus, Web of Science, Scopus) were systematically searched for peer reviewed empirical literature related to campus recreation participatory sport experiences. The results were then screened with predetermined criteria and 180 studies remained for data extraction. Data was extracted and trends were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…This study was limited and delimited in several ways. A primary limitation of this study was the single institutional context, as other recreational sports studies have (Wilson, 2022). However, the researchers were very familiar with the institutional and geographic context of the institution.…”
Section: Limitations and Delimitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was limited and delimited in several ways. A primary limitation of this study was the single institutional context, as other recreational sports studies have (Wilson, 2022). However, the researchers were very familiar with the institutional and geographic context of the institution.…”
Section: Limitations and Delimitationsmentioning
confidence: 99%
“…Here, research has found that on-campus employment is a critical catalyst for career readiness for college students (Astin, 1993; Carr, 2005; Kuh, 2009), yet the field of collegiate recreation has not explored this topic in detail. Wilson's (2022) review of recreational sports scholarship revealed that few empirical articles focus on how collegiate recreation facilitates career readiness. To date, only four studies (Carr, 2005; Burnett, 2021; McFadden & Wallace-Carr, 2015) have focused on how recreational sports student employees develop workplace competencies.…”
mentioning
confidence: 99%